Nigella sativa (black seed) effects on plasma lipid concentrations in humans: A systematic review and meta-analysis of randomized placebo-controlled trials. (April 2016) - Sahebkar, Amirhossein; Beccuti, Guglielmo; Simental-Mendía, Luis E.; Nobili, Valerio; Bo, Simona
Graphical abstract: Abstract: The effects of Nigella sativa (NS) on plasma lipid concentrations are controversial. A systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted to obtain a conclusive result in humans. PubMed-Medline, SCOPUS, Web of Science, and Google Scholar databases were searched (up to August 2015) to identify RCTs investigating the impact of NS on total cholesterol, LDL-cholesterol (LDL-C), HDL-cholesterol (HDL-C), and triglycerides concentrations. A random-effects model and the generic inverse variance weighting method were used for quantitative data synthesis. Meta-regression, sensitivity analysis, and publication bias assessments were performed using standard methods. A total of 17 RCTs examining the effects of NS on plasma lipid concentrations were included. Meta-analysis suggested a significant association between NS supplementation and a reduction in total cholesterol (weighed-mean-difference [WMD]: −15.65 mg/dL, 95% CI: −24.67, −6.63, p = 0.001), LDL-C (WMD: −14.10 mg/dL, 95% CI: −19.32, −8.88, p < 0.001), and triglyceride levels (WMD: −20.64 mg/dL, 95% CI: −30.29, −11.00, p < 0.001). No significant effect on HDL-C concentrations (WMD: 0.28 mg/dL, 95% CI: −1.96, 2.53, p = 0.804) was found. A greater effect of NS seed oil versus seed powder was observed on serum total cholesterol and LDL-C levels, and an increase in HDL-C levels was found only after NS seed powder supplementation. NS has a significant impact on plasma lipid concentrations, leading to lower total cholesterol, LDL-C, and TG levels while increased HDL-C is associated with NS powder only. Further RCTs are needed to explore the NS benefits on cardiovascular outcomes.